Spin correlations in the Drell-Yan process, parton entanglement, and other unconventional QCD effects - Nachtmann, Otto (Annals of physics, 2014)
We review ideas on the structure of the QCD vacuum which had served as motivation for the discussion of various non-standard QCD effects in high-energy reactions in articles from 1984 to 1995. These effects include, in particular, transverse-momentum and spin correlations in the Drell-Yan process and soft photon production in hadron-hadron collisions. We discuss the relation of the approach introduced in the above-mentioned articles to the approach, developed later, using transverse-momentum-dependent parton distributions (TDMs). The latter approach is a special case of our more general one which allows for parton entanglement in high-energy reactions. We discuss signatures of parton entanglement in the Drell-Yan reaction. Also for Higgs-boson production in pp collisions via gluon-gluon annihilation effects of entanglement of the two gluons are discussed and are found to be potentially important. These effects can be looked for in the current LHC experiments. In our opinion studying parton-entanglement effects in high-energy reactions is, on the one hand, very worthwhile by itself and, on the other hand, it allows to perform quantitative tests of standard factorisation assumptions. Clearly, the experimental observation of parton-entanglement effects in the Drell-Yan reaction and/or in Higgs-boson production would have a great impact on our understanding how QCD works in high-energy collisions.